2006
DOI: 10.1177/106689690601400109
|View full text |Cite
|
Sign up to set email alerts
|

VEGF Expression is Associated with Negative Estrogen Receptor Status in Patients with Breast Cancer

Abstract: The aim of this study was to analyze the association between vascular endothelial growth factor (VEGF) expression on tumor cells and other clinicopathologic parameters in breast cancer that could give additional information on its prognostic significance. Immunohistochemical analysis of expression of VEGF, estrogen (ER) and progesterone receptor (PR), HER-2/neu, and Ki67 was performed in 233 breast cancers. VEGF expression estimated semiquantitatively was correlated with all the above-mentioned parameters as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 25 publications
(26 reference statements)
4
29
0
4
Order By: Relevance
“…Another study showed that estrogen regulates VEGF expression but that estrogen receptor is also critical in determining the transcription of VEGF mRNA [46]. Some data suggest that ER and VEGF are inversely correlated; other data imply that estrogen induces VEGF expression and activity [47]. In a clinical case-control study comparing serum VEGF levels of 200 breast cancer patients with 88 healthy controls, it was shown that elevated levels of serum VEGF were observed in patients with invasive ductal cancer, ductal carcinoma in situ, and estrogen-receptor-positive tumors, but not with lobular carcinoma in situ or estrogenreceptor-negative tumors [48].…”
Section: Vegf and Breast Cancermentioning
confidence: 99%
“…Another study showed that estrogen regulates VEGF expression but that estrogen receptor is also critical in determining the transcription of VEGF mRNA [46]. Some data suggest that ER and VEGF are inversely correlated; other data imply that estrogen induces VEGF expression and activity [47]. In a clinical case-control study comparing serum VEGF levels of 200 breast cancer patients with 88 healthy controls, it was shown that elevated levels of serum VEGF were observed in patients with invasive ductal cancer, ductal carcinoma in situ, and estrogen-receptor-positive tumors, but not with lobular carcinoma in situ or estrogenreceptor-negative tumors [48].…”
Section: Vegf and Breast Cancermentioning
confidence: 99%
“…Expression of VEGF-A has been found to be upregulated and suggested to be associated with progression of certain types of human tumours such as lung (Han et al, 2001), eosophageal (Kleespies et al, 2005) and colorectal cancers (Des Guetz et al, 2006). Studies on human breast cancer reported a significant relationship between high expression of VEGF-A and tumours with higher proliferation rate, negative oestrogen receptor status (Fuckar et al, 2006) and poor prognosis (Linderholm et al, 1999).…”
mentioning
confidence: 99%
“…A molecular target of interest in this respect is vascular endothelial growth factor (VEGF)-A. VEGF-A is involved in the development and maintenance of tumor angiogenesis and is involved early during tumorigenesis. Various studies have reported overexpression of VEGF-A in the breast cancer microenvironment, compared with normal breast tissue (2)(3)(4)(5). All VEGF-A splice variants are bound by the clinically used monoclonal antibody bevacizumab.…”
mentioning
confidence: 99%